Synthesis, characterization and structural study of a phosphonium salt containing the [Pd2Br6]2− ion and its application as a novel, efficient and renewable heterogeneous catalyst for amination of aryl halides and the Stille cross-coupling reaction. (17th February 2016) - Naghipour, Ali; Ghorbani-Choghamarani, Arash; Heidarizadi, Fateme; Notash, Behrouz
Graphical abstract: Herein a phosphonium salt containing [Pd2 Br6 ] 2− has been prepared, characterized and applied as recoverable catalyst for the Stille and amination reactions. Abstract: In this study palladium(II) acetate reacts with a phosphonium salt, [Ph3 PCH2 C6 H4 CH2 Br]Br, to give [Ph3 PCH2 C6 H4 CH2 OC(O)CH3 ]2 [Pd2 Br6 ]. Characterization of the obtained compound was performed by elemental analysis, IR, 1 H, 31 P, 13 C NMR and X-ray crystallography. It was found that this compound can act as an efficient catalyst for amination of aryl halides to afford primary amines and satisfactory results were obtained. It has also been successfully employed in the catalytic Stille cross-coupling reaction. The catalyst is easily recoverable and reusable without significant loss of its catalytic activity.